Factors Indicating a Bad Prognosis in Patients of Emphysematous Pyelonephritis with Diabetes - Muhammad Tayyab Naeem, Nadir Hussain, Jamshaid Rahim, Muhammad Umer, Malyka Batool, Muhammad Nasir Ibrahim, Hafiz Shahzad Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate our experience with emphysematous pyelonephritis in a tertiary care facility and to describe our approach. Study design: Cross-sectional retrospective study Place and duration of study: Dept of Urology, Shaikh Zayed Hospital, Lahore from 1st January 2017 to 31st December 2020. Methodology: Thirty six patients who died of emphysematous pyelonephritis out of the 976 patients and between 34-82 years were enrolled. Used classification systems include Wan and Huang. We examined potential predictive indicators for mortality as well as the clinical and treatment characteristics of these patients. Results: There were 2.27 female for every male. Poor prognosis is correlated with advanced grade. The biggest number of unfavourable prognostic variables is accounted for by deranged HbA1C 27.8% and advanced grades 33.3%. However, DIC causing thrombocytopenia 13.9% and hypotensive shock 13.9% are significant causes of mortality in emphysematous pyelonephritis. The low protein content 11.1% has the lowest mortality risk. The most frequent clinical signs were tachycardia in 14, fever in 9, pyuria in 8 and flank pain in 5 patients. Conclusion: Advanced Huang and Tseng Classification grade is the principal reason for death in our study, followed by shock, hypoprotenemia, DIC-induced thrombocytopenia, and elevated HbA1C levels. Keywords: Emphysematous pyelonephritis, Diabetes, Prognostic factor